“LEXICOGRAPHICAL CHARACTERISTICS AND ROLE OF NEOLOGISMS IN ENGLISH” (Modern education and development, 2025)
This article investigates the lexicographic characteristics and the important role of neologisms in the English and Uzbek languages, highlighting their continuous evolution and adaptation to the sociocultural, technological, and global transformations of modern life. Neologisms, or newly coined terms and expressions, emerge as languages respond to new realities in science, technology, politics, and social movements. These terms reflect societal developments such as the rise of digital technologies, changes in communication patterns, and the blending of cultures in an increasingly globalized world. The study focuses on how these neologisms are formed, categorized, and represented in both English and Uzbek lexicons, especially within the context of dictionaries. A significant portion of this research examines how lexicographers document neologisms—assessing factors such as frequency of usage, media influence, and the gradual acceptance of these terms into common discourse. Both English and Uzbek have unique methods of integrating new words, shaped by distinct linguistic, cultural, and historical backgrounds.